2019
DOI: 10.29309/tpmj/2019.26.12.3759
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcome of Sutureless Thyroidectomy by Ligasure small jaw verses conventional technique.

Abstract: ABSTRACT… Thyroid is a highly vascular gland and hemostasis is a key limiting factor in morbidity and mortality in thyroid surgery. Hemostasis has always been a challenge and various techniques have been used. Vessel sealers like Ligasure are now gaining popularity. Objectives: The objective of this study is to compare thyroidectomy by Ligasure with conventional technique in terms of mean operative time and post-operative blood loss. Study Design: It is a Randomized Control Trial. Setting: Surgical Department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Another study done by Grøndal et al (14) found that Using Ligasure in complete thyroidectomy instead of the more traditional suture ligation approach significantly decreased intraoperative blood loss. The same results were also obtained in a study performed by Akram et al (1) found that mean intraoperative blood loss was recorded to be 57.28 ml in the Ligature technique group and 70.854 ml in the conventional technique group, with a P-value of 0.0001, indicating a significant difference between the two groups.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Another study done by Grøndal et al (14) found that Using Ligasure in complete thyroidectomy instead of the more traditional suture ligation approach significantly decreased intraoperative blood loss. The same results were also obtained in a study performed by Akram et al (1) found that mean intraoperative blood loss was recorded to be 57.28 ml in the Ligature technique group and 70.854 ml in the conventional technique group, with a P-value of 0.0001, indicating a significant difference between the two groups.…”
Section: Discussionsupporting
confidence: 82%
“…Hemostasis of blood vessels can be performed using the time-tested Clamp and tie method or more modern methods like Ligasure, a form of bipolar surgical diathermy. The novel electro thermal bipolar tissue sealing device (Ligasure) has been used in many different surgical specialties, and other diathermy approaches have been presented to limit intraoperative blood loss (1) . Thyroid surgery necessitates precise and reliable hemostasis because of the proximity of the thyroid to vital structures such the carotid artery, jugular vein, and recurrent laryngeal nerve (RLN).…”
Section: Introductionmentioning
confidence: 99%
“…21 Similarly, Akram et al found that when thyroidectomy was conducted using Ligasure Small Jaw, the operational duration was reduced from 106 ± 23.5 minutes to 80 ± 12.4 minutes (P=0.006), compared to 106 ± 23.5 minutes for traditional suturing thyroidectomy. 22 Different other studies also have indicated mean operating times for complete thyroidectomy with Ligasure group , ranging from 58 minutes to 115.54 minutes, and mean operative durations for conventional vascular ligation approach ranging from 75 to 153.45 minutes. 3,4 Ozben et al concluded in their study that Ligasure vessel ligation is a safe approach for thyroid surgery with few problems, similar to our findings.…”
Section: Discussionmentioning
confidence: 95%
“…13 The variables of operative time 14 , intraoperative / postoperative blood loss and hospital stay 15 were discussed in many studies but very infrequent data regarding the post-operative pain. In our setting study already conducted on different variables 16 but for post-operative pain we conducted the current study.…”
Section: Discussionmentioning
confidence: 99%